Poorly Differentiated Nonkeratinizing Squamous Cell Carcinoma of the Thymus: Clinicopathologic and Molecular Genetic Study of 25 Cases. (September 2018) - Suster, David; Pihan, German; Mackinnon, Alexander C.; Suster, Saul
Abstract : Thymic carcinoma represents a rare and poorly understood type of thymic epithelial neoplasm that has been the subject of much controversy. Poorly differentiated nonkeratinizing squamous cell carcinoma, also known as lymphoepithelioma-like thymic carcinoma, is a rare variant of thymic carcinoma that has not been adequately characterized in the literature. The clinicopathologic, immunohistochemical, ultrastructural, and molecular features of 25 cases are reported. The patients were 19 men and 6 women, ranging in age from 20 to 85 years (mean: 60 y). The tumors presented clinically as anterior mediastinal masses with chest pain and shortness of breath or were found incidentally on imaging studies. Tumor size ranged from 2.0 to 13.5 cm in greatest diameter. Most of the tumors were small, well-circumscribed and confined to the mediastinum. Five cases presented with large, bulky, and infiltrative masses. Histologically, the hallmark of these tumors was a neoplastic proliferation of large, round to oval cells with vesicular nuclei, prominent eosinophilic nucleoli, and scant cytoplasm. Two histologic growth patterns were identified: tumors with a heavy lymphoplasmacytic stroma (lymphoepithelioma-like pattern), and tumors showing abundant desmoplastic stroma (desmoplastic pattern). Immunohistochemical stains showed strong positivity of the tumor cells for cytokeratin AE1/AE3, CK5/6, CK18, MOC31, p16, p40, and p63. MIB-1 showed on average 35% nuclear positivity. CD117 was positive in 21/25 cases and CD5 in 20/25 cases. Epstein-Barr encoded RNA in situ hybridization was positive in only 1 case. Electron microscopy in 4 cases showed primitive round to oval cells with prominent nucleoli, scant cytoplasm and immature cell junctions. Molecular features were studied by next-generation sequencing using high quality sequence data obtained from 18 patients. Variants with allele frequency between 5% and 45% and quality scores >50 were classified as somatic. A total of 16/18 cases had one or more somatic variants of unknown significance. One case showed an IDH1 p. R132C mutation, also of unknown significance. No "actionable" genes amenable to currently available targeted therapies were identified in this cohort. Clinical follow-up was obtained in 20 patients; 14 patients were alive and well with no evidence of disease between 1.5 and 16 years after diagnosis (median survival: 4 y; mean: 5.5 y). Most survivors had relatively small tumors (<5 cm. diameter), were in stage I and II at diagnosis and showed clear surgical margins. Five patients died of their tumors with metastases to bone, brain, chest wall, lungs and lymph nodes; all were in advanced stages and showed positive margins. Prognosis for these tumors appears to be correlated with the staging and status of the margins at the time of initial surgery. Abstract : Supplemental Digital Content is available in the text.